Effects of Intangible Assets on Financial and Governance Policies - Mehdi Rezaei; MehdiFatemeh RezaeiPoorghaumi (پژوهش‌های تجربی حسابداری, 2018)
Economy has changed evaluation methods of the firms. The major gap between market value and book value of firms is a motivation of extensive research on unexplained value or reserve savings. Empirical studies in developed markets show that intangible assets are strategic and important. The aim of this study is to investigate the influence of intangible assets on fiscal and governance policy in firms listed in the Stock Exchange in Tehran. The sample consists of 78 firms listed in Tehran Stock Exchange during the period from 2007 to 2013. Data is analyzed using correlation analysis method, multiple regression and Wald test. Regression analysis is tested based on panel data and using random effects models. This study is aimed to investigate the relation of intangible assets to fiscal and governance policy variables such as financial structure, the dividend ratio, management ownership, and board structure. The results show that intangible assets have a significant negative relation to financial structure, a significant positive relation to board independence, and no significant relation to dividend. In general, the results indicate that intangible assets have effects on governance policies and they should be more considered